Harnessing an anti-CRISPR protein for powering CRISPR/Cas9-mediated genome editing in undomesticated Bacillus strains - Man Su Kim; Da-Eun Jeong; Soo-Keun Choi (Microbial Cell Factories, 2025)
Abstract Background Wild-type Bacillus strains have significant industrial and medical value, but their effective utilization often requires strain improvement. The CRISPR/Cas9 system has become the primary tool for genome editing, allowing precise introduction of desired mutations at specific chromosomal locations. However, the practical application of CRISPR/Cas9 in most wild-type Bacillus strains remains challenging due to cellular toxicity resulting from Cas9/sgRNA activity. Therefore, controlling Cas9 toxicity is essential for the widespread application of the CRISPR/Cas9 system in wild-type Bacillus strains. Results We employed AcrIIA4, an anti-CRISPR protein that inhibits the Cas9/sgRNA ribonucleoprotein complex from interacting with DNA, to mitigate Cas9/sgRNA-mediated toxicity, thereby enabling CRISPR/Cas9-based genome editing in wild-type strains. The newly constructed CRISPR/anti-CRISPR (CAC) plasmids harbor both cas9 and acrIIA4 genes controlled by the P spac and P xyl promoters, respectively, along with the repressor genes lacI and xylR. This design allows precise control of Cas9 activity through inducers. Xylose, which induces AcrIIA4 expression, effectively alleviated Cas9/sgRNA-mediated toxicity during transformation. Under xylose induction, the CAC plasmid led to a remarkable 139-fold increase in the transformation efficiency of wild-type Bacillus subtilis compared to a plasmid lacking anti-CRISPR. Meanwhile, IPTG induction promoted Cas9 expression, facilitating efficient genome editing. Upon IPTG induction, the genome editing efficiency in wild-type B. subtilis increased from 0 to 95.8% in transformants carrying the CAC plasmid. Importantly, our findings extend beyond B. subtilis, revealing that the anti-CRISPR protein dramatically enhanced transformation and genome editing efficiencies in Bacillus pumilus. Moreover, we demonstrated that the CAC system successfully enabled the generation of spo0A mutants in Bacillus mojavensis, Bacillus tequilensis, and Paenibacillus polymyxa. Conclusions In this study, we developed a CAC system that utilizes the anti-CRISPR protein AcrIIA4 to reduce Cas9/sgRNA-mediated toxicity in Bacillus strains. This system enables precise control of AcrIIA4 and Cas9 expression through inducers, significantly enhancing the efficiency of transformation and genome editing in wild-type Bacillus strains. Therefore, the CAC system stands as a powerful tool to facilitate genome editing in diverse wild-type Bacillus species.